ELASTIC CHARACTERISTICS OF ANNULAR HUBS IN ULTRA SOUND SYSTEMS - I. V. Lugovoj; V. P. Lugovoj (Наука и техника)
The paper provides a justification for application of elastic ring hubs with variable cross-section of ultra sound systems. The results of theoretical calculations and experimental investigations of elastic characteristics of annular hubs.